Effects of water stress on protective enzyme activities and lipid peroxidation in different Salvia miltiorrhiza Bunge varieties at seedling stage - LU Ping; ZHANG Li; WANG Meng; WANG Tao; JIANG Yuanyuan (浙江大学学报. 农业与生命科学版)
The dried root and rhizome of Salvia miltiorrhiza Bunge (Lamiaceae, Salvia), one of the popular traditional Chinese medicine (TCM), is officially listed in Chinese pharmacopoeia under the name of Danshen. S. miltiorrhiza have been widely used for treatment of coronary heart disease, cerebrovascular disease, neurasthenic insomnia, bone loss, liver fibrosis, hepatocirrhosis and chronic renal failure. Waterlogging is abiotic stress that influences species composition and productivity in numerous plant communities worldwide. For most crops, excess water is a major constraint to productivity in many regions and situations, and the inability of crops to withstand low oxygen conditions in the root zone will lead to yield losses. Zhongjiang County was the genuine producing areas with a long history for the plant of Danshen. But now, the effect mechanism of water stress on S. miltiorrhiza was little known.The objective of this study was to elucidate the physiological responses of different S. miltiorrhiza under water stress. The finite element method can be used as academic base for flooding resistance mechanisms, and provide evidence for breeding S. miltiorrhiza varieties and improving the cultivation technology of resistance to waterlogging.The experiment was conducted in 2010—2011 at the experimental station of Sichuan Agricultural University, Ya'an, Sichuan Province, China. Tissue cultured lobular S. miltiorrhiza, tissue cultured big-leaf S. miltiorrhiza, tetraploid lobular S. miltiorrhiza, tall big-leaf S. miltiorrhiza, dwarf big-leaf S. miltiorrhiza and wild S. miltiorrhiza in Zhongjiang were obtained from Zhongjiang County, Sichuan Province. All materials were maintained in a rain shelter. The waterlogging treatment was mimicked by treating pot plants with flooding. Investigations were carried out on the changes of malondialdehyde (MDA) content, superoxide dismutase (SOD), peroxidase (POD), catalase (CAT) activities and proline (Pro) content of six S. miltiorrhiza varieties.The result indicated that waterlogging stress of 5 days was the optimum condition for the simulation of waterlogging stress. Each variety had different physiological and biochemical response to waterlogging stress. Under the flooding stress, SOD and CAT activity of tissue cultured big-leaf S. miltiorrhiza was the highest, and that of tissue cultured lobular S. miltiorrhiza was the lowest; POD activity of dwarf big-leaf S. miltiorrhiza was the highest, and that of tissue cultured lobular S. miltiorrhiza was the lowest; Tetraploid lobular S. miltiorrhiza contained the most contents of Pro and MDA, while the wild S. miltiorrhiza in Zhongjiang contained the least content of Pro; Tissue cultured big-leaf S. miltiorrhiza, tall big-leaf S. miltiorrhiza and Dwarf big-leaf S. miltiorrhiza contained the same content of MDA which were lower than the other three varieties. Correlation analysis showed that there was no prominent correlation among all these indexes. Actually, they have independent functions. Therefore, each one can be regarded as physiological index of water tolerance for S. miltiorrhiza.In conclusion, the research results suggested that: 1) Waterlogging stress of 5 days was the optimum condition for the simulation of waterlogging stress. 2) Each variety of S. miltiorrhiza had different physiological and biochemical response to waterlogging stress. 3) Each index can be regarded as physiological trait of water tolerance for S. miltiorrhiza seedlings.